Barley Anther and Meiocyte Transcriptome Dynamics in Meiotic Prophase I - Barakate, Abdellah; Orr, Jamie; Schreiber, Miriam; Colas, Isabelle; Lewandowska, Dominika; McCallum, Nicola; Macaulay, Malcolm; Morris, Jenny; Arrieta, Mikel; Hedley, Pete E.; Ramsay, Luke; Waugh, Robbie (Frontiers in Plant Science, 2021)
In flowering plants, successful germinal cell development and meiotic recombination depend upon a combination of environmental and genetic factors. To gain insights into this specialised reproductive development programme we used short- and long-read RNA-sequencing (RNA-seq) to study the temporal dynamics of transcript abundance in immuno-cytologically staged barley (Hordeum vulgare) anthers and meiocytes. We show that the most significant transcriptional changes in anthers occur at the transition from pre-meiosis to leptotene–zygotene, which is followed by increasingly stable transcript abundance throughout prophase I into metaphase I–tetrad. Our analysis reveals that the pre-meiotic anthers are enriched in long non-coding RNAs (lncRNAs) and that entry to meiosis is characterized by their robust and significant down regulation. Intriguingly, only 24% of a collection of putative meiotic gene orthologues showed differential transcript abundance in at least one stage or tissue comparison. Argonautes, E3 ubiquitin ligases, and lys48 specific de-ubiquitinating enzymes were enriched in prophase I meiocyte samples. These developmental, time-resolved transcriptomes demonstrate remarkable stability in transcript abundance in meiocytes throughout prophase I after the initial and substantial vast reprogramming at meiosis entry and the complexity of the regulatory networks involved in early meiotic processes.